Design of Materials for Bone Tissue Scaffolds - Boccaccio, Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book proposes extensive and varied design strategies for bone tissue engineering. The design process of materials for bone tissue scaffolds presently represents an issue of crucial importance and is being studied by many researchers throughout the world. A number of studies have been conducted, aimed at identifying the optimal material, geometry, and surface that the scaffold must possess to stimulate the formation of the largest amounts of bone in the shortest time possible.